Comparative analysis on: Metacognition and Mindfulness in twins with Attachment and children with ASD through I.C.T. - Sideraki, Angeliki; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The following study examines the neuroscience of attachment and the role of mindfulness and metacognition. First, the importance of mindfulness is discussed, which is strongly found in people with attachment, particularly in twins. Next, mindfulness in people with autism is examined. More specifically, the purpose of the research is to draw conclusions about the emotional intelligence that individuals with ASD develop and the levels of mindfulness and metacognition that they are able to achieve. In the course of the study, reference is made to the factors that influence their emotional development such as stress and vortices, where its role seems to be different compared to typically developing individuals because individuals with autism follow a different developmental and cognitive trajectory. Then, topic is made to the essential role of AI( artificial intelligence), which seems contribute positively to the cognitive and emotional development of children with autism as various important technologies are used, such as specially constructed and functional robots, which contribute to both the treatment and diagnosis of autism. From the present study, it was found that all the above methods contribute to improve the cognitive level of individuals with autistic disorder and to raise them to the levels of metacognition pyramid and knowledge-cognition pyramid. Finally, the role of ICT and AI is particularly helpful in achieving this ascent